Penatalaksanaan Holistik Tinea Kruris dan Obesitas Derajat I Pada Ny. J Usia 43 Tahun Di Puskesmas Kota Karang Melalui Pendekatan Kedokteran Keluarga - Gusti Agung Putu Yogy Veda Ananta Gusti; Chika Tania; Sahab H. Sibuea (Medula, 2022)
Dermatophytosis infections have spread throughout the world. The prevalence of this disease is 20-25% with the most common cause being dermatophyte fungi, while the most common in Asia is tinea corporis infection with a prevalence of 35.40%. Implement a holistic approach to family medicine and comprehensively in detecting internal and external risk factors and solve problems based on Evidence Based Medicine that is family-approached and patientcentered. This study is descriptive study about case report. The primary data obtained through anamnesis, physical examination and a visit to the home. Secondary data were obtained from medical records of patients. The patient complained of reddish spots on the right left groin since 4 days ago. The patient also admitted that she could easily sweat and not ooften change her clothes. Diagnosis and management of this patient has been doing holistically, patients center, family approach based on several theories and current research that not just focused on the patient but to the other member of her familiy so it would resulting in an increase of cognitive and life quality on tinea cruris and obesity patient.